2020
DOI: 10.2174/1874434602014010248
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Induced Abortion and its Associated Factors among Female Students of Health Science in South West Ethiopia

Abstract: Background: Globally, approximately 180-200 million pregnancies occur each year, about 75 million are unwanted pregnancies. The majority of unwanted pregnancies end in induced abortions each year. Combating abortion, abortion-related morbidity and mortality by preventing unwanted pregnancy has a great role in decreasing maternal mortality. Induced abortions, specifically unsafe abortion, are an important public health concern in developing countries. Nursing professionals encounter cases in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 7 publications
(1 reference statement)
0
9
2
Order By: Relevance
“…Due to negative socio-cultural norms, young women are frequently refused access to family planning services, which increases their risk of unwanted pregnancies that may result in abortion. The finding was significantly lower than that of study conducted in Ethiopia [ 19 , 31 ], Nepal [ 16 ], Africa [ 15 ]. The difference in the study population and the improvement in maternal health care service accessibility and utilization over time could be the possible explanation.…”
Section: Discussioncontrasting
confidence: 74%
“…Due to negative socio-cultural norms, young women are frequently refused access to family planning services, which increases their risk of unwanted pregnancies that may result in abortion. The finding was significantly lower than that of study conducted in Ethiopia [ 19 , 31 ], Nepal [ 16 ], Africa [ 15 ]. The difference in the study population and the improvement in maternal health care service accessibility and utilization over time could be the possible explanation.…”
Section: Discussioncontrasting
confidence: 74%
“…All studies included in this systematic review and meta-analysis were cross-sectional [7,8,16,[18][19][20][21][22][23]34]. The sample size of the studies ranged from 213, a study done at Addis Ababa University [18] to 813, another study done in Arba Minch town [7].…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…A multilevel analysis based on the 2016 Ethiopian Demographic Health Survey (EDHS) also showed that the magnitude of abortion among youths was 2.5% [6]. The magnitude of induced abortion among higher education institution female students in Ethiopia ranged from 2.8% to 18.8% [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations